Anxiety sensitivity, anxiety, depression and psychophysical characteristics of premenstrual period - Staničić, Ana (2008)
Aim of this study was to investigate anxiety sensitivity, anxiety and depression in relation to psychophysical characteristics of the premenstrual period. Psychophysical characteristics are defined as assessments of the physical state (fatigue, breast tenderness, bloating and lack of sleep), emotional sense (happiness, anger, sadness, irritability, anxiety and distraction) and general assessments of physical attractiveness and satisfaction with oneself. Diary of symptoms of PMS was designed for this study as well as a socio-demographic questionnaire and a menstrual cycle calendar. The study entailed keeping a diary of symptoms a week before menstruation and four days one week after the onset of menstruation, during two menstrual cycles. Anxiety sensitivity was measured with ASI (McNally, Reiss, Peterson & Gursky, 1986), anxiety with STAI (Spielberger, 1968) and depression with BDI (Beck, 1987) ; they were all measured once at the begining of the study. The study was conducted on a convenient sample (N=51). The premenstrual period, in regard to the period after menstruation, is characterized by higher intensities of negative emotions and certain physical states, and lower intensities of feelings of physical attractiveness and satisfaction with oneself, regardless of the level of anxiety sensitivity, anxiety or depression. Anxiety sensitivity, anxiety and depression were significant predictors of emotional sense variables and general assessments of physical attractiveness and satisfaction with oneself ; with much higher predictive value in the period after menstruation than the premenstrual period.